2015
DOI: 10.1002/ccd.26324
|View full text |Cite
|
Sign up to set email alerts
|

Fate of fenestration in children treated with fontan operation

Abstract: Spontaneous closure and favorable result in test occlusion are more common in tube than in window fenestrations. Since most preoperative anatomic and hemodynamic factors were similar in all patient groups, we find it difficult to predict the fate of a window-type fenestration and the result of test occlusion. © 2015 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…With each modification, fenestration patency has remained a primary concern, as 8% to 40% of fenestrations close spontaneously within 3 months 9,13 . Spontaneous closure rates can increase to 64% in tube fenestrations, compared with window‐type fenestrations 14 . In addition, Bando et al 11 found that despite anticoagulation, 64% of large (>4 mm) fenestrations vs 90% of small (2.5 mm) fenestrations closed spontaneously within 1 year of the procedure.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…With each modification, fenestration patency has remained a primary concern, as 8% to 40% of fenestrations close spontaneously within 3 months 9,13 . Spontaneous closure rates can increase to 64% in tube fenestrations, compared with window‐type fenestrations 14 . In addition, Bando et al 11 found that despite anticoagulation, 64% of large (>4 mm) fenestrations vs 90% of small (2.5 mm) fenestrations closed spontaneously within 1 year of the procedure.…”
Section: Figurementioning
confidence: 99%
“…9,13 Spontaneous closure rates can increase to 64% in tube fenestrations, compared with window-type fenestrations. 14 In addition, Bando et al 11 found that despite anticoagulation, 64% of large (>4 mm) fenestrations vs 90% of small (2.5 mm) fenestrations closed spontaneously within 1 year of the procedure. While small fenestrations are associated with earlier closure and high systemic venous pressure, large fenestrations are associated with significant arterial desaturation.…”
mentioning
confidence: 99%
“…The reported incidence of catheter-based interventions (that is, excluding diagnostic cardiac catheterization without intervention) varies heavily; 3 to 65% of patients require at least one additional catheter intervention following Fontan completion 31 , 56 , 57 , 59 , 71 . The most common catheter interventions are fenestration closure (10 to 64% of patients with a fenestration require catheter-based fenestration closing 56 , 57 , 59 , 72 ), occlusion of veno-venous or aortopulmonary collaterals (incidence of 10 to 20%) 57 , 59 , and stenting and dilation of (all types of) obstructions in the Fontan pathway (incidence of 6 to 19%) 57 , 59 , 73 .…”
Section: State Of the Artmentioning
confidence: 99%